Circular antisense oligonucleotides inhibit growth of chronic myeloid leukemia cells. - Rowley, P. T. (The Feinstein Institute for Medical Research, 1999)
BACKGROUND: Antisense represents a conceptually powerful method for regulating gene expression. However, antisense oligonucleotides developed to date manifest two serious limitations-nuclease susceptibility and nonspecific hybridization. Circular oligonucleotides may be superior to conventional linear oligonucleotides in both respects. First, circular agents, having no ends, are exonuclease-resistant. Second, they bind to complementary strands of RNA and DNA with a higher affinity than corresponding linear agents. METHODS AND RESULTS: We assessed the activity of circular phosphodiester deoxynucleotides using chronic myeloid cell lines by targeting polypurine sequences. To represent cells having a bcr3/abl2-type junction, we used K562 cells. A circle targeting a bcr polypurine sequence 385 nucleotides 5' to the junction decreased the cell number by day 5 with an IC(50) of 9 microM. To represent cells having a bcr2/abl2-type junction, we used BV173 cells. A circle targeting the bcr-abl junction itself decreased the cell number by day 7 with an IC(50) of 8 microM. Control oligonucleotides, whether the same sequence uncircularized or circles with the same nucleotide composition but in scrambled sequence, had little effect. Unlike linear agents, circles were stable when incubated in 10% serum. The amount of bcr-abl protein detected by Western blotting using a specific anti-bcr-abl antibody at 24 hr in antisense-treated BV173 cells was only 10% of that of cells treated with control circles, which demonstrates an antisense mechanism of action. CONCLUSIONS: Circular oligodeoxyribonucleotides (1) inhibit the accumulation of CML cells, (2) decrease the amount of bcr-abl protein per cell, (3) have sequence-selective activity, and (4) are more active than linear oligonucleotides containing only the base-pairing region.